2009
DOI: 10.1097/aog.0b013e3181bc6e15
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Cesarean Delivery for Fetal Bradycardia

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 18 publications
1
25
4
1
Order By: Relevance
“…The present study found a significant negative correlation between BDI and UApH, which was inconsistent with the findings reported by Leung et al [2]. They found a significant correlation between BDI and UApH in pregnancies with intrapartum bradycardia due to irreversible causes, but not with reversible or unknown causes.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The present study found a significant negative correlation between BDI and UApH, which was inconsistent with the findings reported by Leung et al [2]. They found a significant correlation between BDI and UApH in pregnancies with intrapartum bradycardia due to irreversible causes, but not with reversible or unknown causes.…”
Section: Discussioncontrasting
confidence: 77%
“…The difference in BDI range between the 2 studies could explain the inconsistency in these results. In the study by Leung et al [2], BDIs were all within 30 minutes, whereas in the present study, the BDI ranged from 11 to 47 minutes. Inclusion of transported cases in our study may have caused this difference.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Ideally, the most valid immediate measures to determine perinatal outcome include the five-minute Apgar score, umbilical cord acid-base balance and the presence of neonatal encephalopathy; use of five-minute Apgar scores alone is a relatively restricted measure of fetal hypoxia. 7,18 Unfortunately, in the current study, perinatal outcomes were assessed by Apgar scores and SCBU admissions, as there were no facilities available to assess cord pH. In addition, the rate of neonatal convulsions could not be compared according to DDI category as data were not available for the 0-30 minutes and 31-60 minutes groups.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Other studies have also emphasised the importance of a 30-minute interval for safe neonatal outcomes. 7,8 However, there is currently little evidence that a DDI of ≤30 minutes is the norm in emergency CS cases. 9 In particular, achieving a DDI of ≤30 minutes in cases of fetal intolerance to labour can be very challenging.…”
Section: Application To Patient Care -In the Current Study It Was Fomentioning
confidence: 99%